PENERAPAN BIMBINGAN KLASIKAL METODE JIGSAW UNTUK MENINGKATKAN HUBUNGAN SOSIAL PERTEMANAN SEBAYA: Application Of Classical Guidance With The Jigsaw Method To Improve Peer Social Relationships - Ibrahim Muhammad Yusuf Zakaria; Denok Setiawati; Koes Widjanarko (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2023)
The problem of social relationships between peers among students is often an important problem in the scope of education. Lack of socializing results in conflicts between friends. The purpose of this study was to see whether social relationships can be improved by using the Jigsaw method on grade X students in Senior High Schools. The method used is Classroom Action Research by implementing 4 stages planning, action, observation, and reflection. The study was conducted with 2 cycles where there was an increase with the implementation of classical guidance with the jigsaw method, in the results of cycle I the percentage value showed 48,5% with enough category then in cycle II it increased to 81,7% with a high category. So it can be concluded that the classroom action research was successful